Vocal acoustic analysis - Jitter, Shimmer and HNR parameters - Teixeira, João Paulo (2014)
A new procedure for Dutomatic diagnosis of pathologies of lhe larynx is presented. The new procedure has the advantage over other traditional techniques an being non-invasive, inexpensive and objective.